Integrated technological approaches to reduce the sodium content in beef burgers - Araújo, Chimenes Darlan Leal de (2026)
This Ph.D. The thesis investigated innovative technological strategies to reduce the sodium content in beef burgers while mitigating technological, physicochemical, and sensory losses. The work integrated experimental and statistical approaches to improve the understanding of sensory characteristics of the product and consumer behavior. To this end, three independent yet complementary studies were conducted, each presented in the form of scientific articles. The first article, presented in the second chapter of the Thesis, evaluated the combined use of micronized salt (MS) and ultrasound (US) to reduce sodium in beef burgers. Ten treatments were formulated by varying the MS concentration and the US application time. The treatment containing 0.75% MS subjected to 10 minutes of US enabled a 50% reduction in sodium while maintaining the texture profile (hardness, springiness, cohesiveness, and chewiness), reducing cooking losses, and preserving color. The second article, presented in the third chapter of the Thesis, expanded this investigation by analyzing the instrumental and sensory effects of the combined application of MS and US in sodium-reduced beef burgers. Physicochemical, technological, texture, instrumental color, and volatile compound analyses were carried out, along with descriptive sensory analysis (DA), Temporal Dominance of Sensations (TDS), and consumer acceptance testing. The combination of technologies enabled a 50% reduction in sodium content without compromising texture, color, or functionality, and also enhanced volatile compounds associated with flavor. Sensory methods indicated a decrease in negative attributes and an increase in positive attributes in US-treated samples, demonstrating that the technologies preserve sensory quality and increase product appeal. Finally, the third study, presented in the fourth chapter of the Thesis, evaluated consurner perception of beef burger packages containing different claims related to sodium-reduction technologies, also considering the ímpact of the “high in sodium” front-of-pack waming. ln a 2x4 factorial design, eight labels were evaluated by 412 consumers through conjoint analysis and cluster formation. The presence of the waming significantly reduced purchase intention, whereas technological claims increased product attractiveness, especially when they emphasized the preservation of salty taste. Technological innovations accounted for 61.1% of the variance in purchase intention, surpassing the negative effect of the warning, indicating that clear communication of technological and sensory benefits can mitigate the impact of nutritional warnings. Taken together, the results of the three studies demonstrate that the combination of MS and US is an effective strategy for reducing sodium content in beef burgers while preserving quality attributes and enhancing consumer acceptance. Moreover, they show that transparent communication regarding these technologies can positively influence consumer perception, providing scientific support for the development and communication of healthier beef burgers.